The Effect Of Education On Correct Breastfeeding Techniques Using Breast Model On Breastfeeding Behavior In Postpartum Mothers - Meria Turnip; Nikmah Jaliliah Ritonga; Elvi Era Liesmayani; Ulfah Khomaina Aulia (JURNAL KEBIDANAN KESTRA (JKK), 2025)
The postpartum period is a crucial period for the success of exclusive breastfeeding. A mother's understanding of proper breastfeeding techniques is one of the factors influencing breastfeeding success. Education using demonstration media such as breast models can improve mothers' understanding and skills in breastfeeding. This study aims to determine the effect of education on proper breastfeeding techniques using breast models on breastfeeding behavior in postpartum mothers at the Nining Pelawati Midwife Clinic in Lubuk Pakam. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample in the study was 18 respondents selected using a purposive sampling technique. Data were collected through a breastfeeding behavior questionnaire before and after education. The results of the analysis showed a significant increase in breastfeeding behavior after education was provided, with a p-value of 0.015 (p <0.05). Therefore, it can be concluded that education on proper breastfeeding techniques using breast models is effective in improving breastfeeding behavior in postpartum mothers. Therefore, the use of demonstration media in breastfeeding education is highly recommended in health care facilities. in health care facilities.